2011
DOI: 10.1007/s13353-011-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a wheat -Thinopyrum ponticum partial amphiploid and its derived substitution line for resistance to stripe rust

Abstract: Stripe rust (caused by Puccinia striiformis) occurs annually in most wheat-growing areas of the world. Thinopyrum ponticum has provided novel rust resistance genes to protect wheat from this fungal disease. Wheat - Th. ponticum partial amphiploid line 7430 and a substitution line X005 developed from crosses between wheat and 7430 were resistant to stripe rust isolates from China. Genomic in situ hybridization (GISH) analysis using Pseudoroegneria spicata genomic DNA as a probe demonstrated that the partial amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…Further, PCR markers based on conserved genetic regions show high levels of collinearity among the cereal genomes, such as rice, Brachypodium, and wheat [Ishikawa et al, 2007]. We previously used PLUG markers to identify chromosomal introgressions from Thinopyrum intermedium [Hu et al, 2011a], T. ponticum [Hu et al, 2011b], and Secale africanum [Lei et al, 2012] and its subsequent assignment to the corresponding linkage group. In the present study, the wheat chromosome group-2 PLUG markers detected polymorphic fragments specific to the D. breviaristatum chromosome in D11-5 ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further, PCR markers based on conserved genetic regions show high levels of collinearity among the cereal genomes, such as rice, Brachypodium, and wheat [Ishikawa et al, 2007]. We previously used PLUG markers to identify chromosomal introgressions from Thinopyrum intermedium [Hu et al, 2011a], T. ponticum [Hu et al, 2011b], and Secale africanum [Lei et al, 2012] and its subsequent assignment to the corresponding linkage group. In the present study, the wheat chromosome group-2 PLUG markers detected polymorphic fragments specific to the D. breviaristatum chromosome in D11-5 ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…ponticum and 1-27, and the result of BLAST also supported that it belongs to the group 7. Similarly, Hu et al (2011) sequenced the amplification of the EST-STS marker MAG2114 on specific bands from wheat-Thinopyrum ponticum substitution line X005, and sequence analysis confirmed that the introduced Th. ponticum chromosomes belonged to homologous group 6.…”
Section: Discussionmentioning
confidence: 92%
“…ponticum, where there is a lack of molecular biology information, the transfer of wheat molecular markers to the species is a feasible method for genetic analysis (Dobrovolskaya et al 2009). Over the last two decades, SSR markers have been used extensively as a effective tool for the genetic analysis of alien chromosomes in various species, such as Thinopyrum ponticum (Hu et al 2011), Thinopyrum intermedium (Lin et al 2007), Triticum timopheevii (Uhrin et al 2012), Leymus mollis (Zhao et al 2013) and Secale cereale (Tang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to locate the breakpoints of the translocation chromosomes, 3AL-specific primers were designed based on the GSP web platform for the target regions. PCR was performed as described by Hu et al [2011b].…”
Section: Molecular Marker Analysismentioning
confidence: 99%